Helium and methane sources and fluxes of shallow submarine hydrothermal plumes near the Tokara Islands, Southern Japan - Wen, Hsin-Yi (Sci Rep, 2016)
Shallow submarine volcanoes have been newly discovered near the Tokara Islands, which are situated at the volcanic front of the northern Ryukyu Arc in southern Japan. Here, we report for the first time the volatile geochemistry of shallow hydrothermal plumes, which were sampled using a CTD-RMS system after analyzing water column images collected by multi-beam echo sounder surveys. These surveys were performed during the research cruise KS-14-10 of the R/V Shinsei Maru in a region stretching from the Wakamiko Crater to the Tokara Islands. The (3)He flux and methane flux in the investigated area are estimated to be (0.99–2.6) × 10(4) atoms/cm(2)/sec and 6–60 t/yr, respectively. The methane in the region of the Tokara Islands is a mix between abiotic methane similar to that found in the East Pacific Rise and thermogenic one. Methane at the Wakamiko Crater is of abiotic origin but affected by isotopic fractionation through rapid microbial oxidation. The helium isotopes suggest the presence of subduction-type mantle helium at the Wakamiko Crater, while a larger crustal component is found close to the Tokara Islands. This suggests that the Tokara Islands submarine volcanoes are a key feature of the transition zone between the volcanic front and the spreading back-arc basin.